PEMBUATAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS WEB MENGGUNAKAN METODE K-MEANS - Tiratana, Aryanatta Paramita; Mulyawan, Bagus; Lauro, Manatap Dolok (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
PT. Sugi Jaya Mandiri is a company specializing as a vendor of industrial equipment. The company has issues in regard of sales data processing and customer service, where the company manually process. Another point to mention is the company's limitations regarding customer service, where customer's inquiries and/or consultations must be sent manually, either by phone or email, thus customers have virtually no channels in which to voice suggestions, critiques and/or complaints towards the company. Considering the company's substantial amount of customers, the current method proves ineffective to provide an adequate service for the customers. It is hoped to make it easier to process customer and sales transaction data, and improving relations between the company and the customers using the potential customer selection feature using the K-Means method. The data used for customer clustering is the company's sales transaction data covering one year time period, starting from 2017. From the clustering results, it could be shown that there is a group of potential customers, totalling four customers and non-potential customers totalling forty customers. Evaluation results using the Silhouette Coefficient method in figuring the potential customer and non-potential customer using K-Means method is 0.85.